Immunodeficiency in children starting antiretroviral therapy in low-, middle- and high-income countries - Koller, Manuel (J Acquir Immune Defic Syndr, 2015)
BACKGROUND: The CD4 cell count or percent (CD4%) at the start of combination antiretroviral therapy (cART) are important prognostic factors in children starting therapy and an important indicator of program performance. We describe trends and determinants of CD4 measures at cART initiation in children from low-, middle- and high-income countries. METHODS: We included children aged <16 years from clinics participating in a collaborative study spanning sub-Saharan Africa, Asia, Latin America and the United States of America (USA). Missing CD4 values at cART start were estimated through multiple imputation. Severe immunodeficiency was defined according to World Health Organization criteria. Analyses used generalized additive mixed models adjusted for age, country and calendar year. RESULTS: 34,706 children from nine low-income, six lower middle-income, four upper middle-income countries and one high-income country (United States of America, USA) were included; 20,624 children (59%) had severe immunodeficiency. In low-income countries the estimated prevalence of children starting cART with severe immunodeficiency declined from 76% in 2004 to 63% in 2010. Corresponding figures for lower middle-income countries were from 77% to 66% and for upper middle-income countries from 75% to 58%. In the USA, the percentage decreased from 42% to 19% during the period 1996 to 2006. In low- and middle-income countries infants and children aged 12-15 years had the highest prevalence of severe immunodeficiency at cART initiation. CONCLUSIONS: Despite progress in most low- and middle-income countries, many children continue to start cART with severe immunodeficiency. Early diagnosis and treatment of HIV-infected children to prevent morbidity and mortality associated with immunodeficiency must remain a global public health priority.